Profil Anisometropia pada Orang Dewasa di Rumah Sakit Ibnu Sina Makassar - Tonang, Eka Uthami; Syawal, Sitti Rukiah; Amir, Suliati P.; Novriansyah, Zulfikri Khalil; Kusumawardhani, Sri Irmandha; Aulia, Nur (Wal'afiat Hospital Journal, 2024)
Anisometropia is an interocular asymmetric refractive condition and is caused by a significant difference in diopters between the right and left eyes. Anisometropia occurs when there is a difference in the refractive power of the two eyes. Classification of several levels of difference, namely 1) difference in refraction between the two eyes less than 1.5 D, where both eyes can still be used together with good fusion and stereoscopic, 2) difference in refraction between the two eyes 1.5 D to 3.0 D (the presence of cylindrical differences is more significant than spherical), and 3) the difference in refraction is more than 3.0 D. The high incidence of Anisometropia can be caused by a lack of community initiative in seeking health assistance to treat Anisometropia, or even prevent Anisometropia from getting worse. The aim of this study was to determine the characteristics of Anisometropia in adults at Ibnu Sina Hospital Makassar. This research is descriptive in nature. The population of this study was all Anisometropia patients registered at Ibnu Sina Hospital Makassar so that the research sample was obtained by total sampling, namely the entire study population of 20 patients. Sample acquisition was adjusted to the inclusion criteria, namely Anisometropia patients with complete medical record data. The data was processed using the univariate method so that the research results showed that the majority of Anisometropia patients at the eye clinic at Ibnu Sina Hospital Makassar were on average 18-25 years old (45%) and mostly occurred in women (60%) and most were students (40%). %) The incidence of Anisometropia is probably caused by excessive use of cellphone or laptop gadgets and at very close range.